ChemInform Abstract: Copper‐Catalyzed Inter‐ and Intramolecular C—N Bond Formation: Synthesis of Benzimidazole‐Fused Heterocycles. Issue 6 (21st January 2016) - Rasheed, Sk.; Rao, D. Nageswar; Das, Parthasarathi
Abstract: The reaction cascade combines a Chan—Lam type coupling and a subsequent Ullmann type coupling.